2006
DOI: 10.1186/1472-6963-6-150
|View full text |Cite
|
Sign up to set email alerts
|

Possible criteria for inpatient psychiatric admissions: which patients are transferred from emergency services to inpatient psychiatric treatment?

Abstract: Background: Patients with psychiatric problems often seek help and assistance in hospital emergency departments. An important task of emergency room staff is to decide whether such patients need to be admitted or whether they can be treated on an outpatient basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
34
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 12 publications
9
34
1
2
Order By: Relevance
“…Although we found no significant differences between women and men in any of the diagnoses, there was a gender difference in having previously received treatment, which is in line with some other studies (Lindamer et al, 2003; Ziegenbein et al, 2006), and with Finnish general population figures [7% women, 4% men seeking mental health treatment in 1 year; (Alha and Pirkola, 2006)]. Most of these offenders had been in psychiatric treatment at some point, and even at the time of offending one third of the women and only slightly fewer men had on‐going contact with the psychiatric services; the gender difference in previous mental health treatment had faded away by the time of the index offence.…”
Section: Discussionsupporting
confidence: 93%
“…Although we found no significant differences between women and men in any of the diagnoses, there was a gender difference in having previously received treatment, which is in line with some other studies (Lindamer et al, 2003; Ziegenbein et al, 2006), and with Finnish general population figures [7% women, 4% men seeking mental health treatment in 1 year; (Alha and Pirkola, 2006)]. Most of these offenders had been in psychiatric treatment at some point, and even at the time of offending one third of the women and only slightly fewer men had on‐going contact with the psychiatric services; the gender difference in previous mental health treatment had faded away by the time of the index offence.…”
Section: Discussionsupporting
confidence: 93%
“…Goldberg et al (33) found that presence of psychosis, a suicide plan, and a history of past suicide attempts predicted hospitalization of adults presenting with suicidal ideation for emergency care. As found in the present study, suicidality was the strongest predictor of admission from ED (34).…”
Section: Discussionsupporting
confidence: 69%
“…While the decision on admission is made primarily on the basis of clinical assessment and the diagnosis rendered. However, other, possibly unknown or obscure criteria may also have an important influence on the rate of admissions (Ziegenbein, Anreis, Brüggen, Ohlmeier, & Kropp, 2006 ). Even in those cities with mental health legislation, the principles like “impairment of mental function” and “need for treatment” were oversimplified and permitted different interpretations.…”
Section: Discussionmentioning
confidence: 99%